Strategies to Increase Willingness to Receive a COVID-19 Vaccine among Nursing Home Staff - Lisa S. van Tol; Wendy Meester; Monique A. A. Caljouw; Wilco P. Achterberg (MDPI AG, 2022)
Background: Nursing home (NH) staff and residents have been prioritized to receive COVID-19 vaccinations. However, NH staff have been hesitant. This study explored what strategies were used to overcome this hesitancy and which of these were found to be important by NH staff to increase their willingness to take a COVID-19 vaccine. Methods: This study employed a sequential exploratory qualitative design. The COVID-19 MINUTES study aimed to describe the challenges presented by, responses to, and impact of the COVID-19 pandemic in NHs. The minutes of COVID-19 outbreak teams (COTs) in Dutch long-term care organizations (n = 41) were collected and coded using content analysis. Textual units from December 2020 to April 2021 that regarded strategies to increase staff's vaccination willingness (n = 67) were selected. Subsequently, to validate these data, two panels of NH healthcare workers (HCWs) and policy workers (PWs) (n = 8) selected, discussed, and ranked the strategies that they found to be important using a modified nominal group technique. Results: The strategies described in the minutes included financial reimbursements, personal contact, story sharing, logistics support, role models, visual information, and written information. Except for financial reimbursement, all these strategies were considered important or very important by the panel participants. Some organizations combined multiple strategies. Conclusion: The strategies that were found important in combination may be used more broadly and should be developed further with the involvement of HCWs.